Lingualand Media Development to Improve Beginning Reading Abilities of 5-6 Year-Old Children - Miftah Dilla; Ria Novianti; Rita Kurnia (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
This study developed the digital learning media "Lingualand" to improve the early reading skills of children aged 5–6 years. Conducted at TK Al Fattaah Sawah Baru, Kampar, the study used the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with subjects including content experts, media experts, linguists, educators, and 5–6-year-old children. Data were collected through observation, questionnaires, and documentation, then analyzed descriptively and quantitatively. Initial results showed early reading ability was in the emerging category (36.88%). Lingualand was developed as an interactive application containing letter recognition, vowels and consonants, and Malay-Riau cultural vocabulary with engaging audio and visuals. Validation indicated very high feasibility: content experts (87.50%), media experts (84.62%), linguists (87.50%), and educators (88.18%). A limited trial produced 95.31% (very high). Thus, Lingualand is deemed suitable as an interactive learning medium to improve early reading skills in young children.